EFFECTIVENESS OF LEGAL ENFORCEMENT OF INTELLECTUAL PROPERTY RIGHTS IN CYBERSPACE - Filinovych, Valeria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: this scientific research is devoted to the study and analysis of best practices which show the effectiveness of legal enforcement of intellectual property rights in cyberspace, their comparison and development on their basis of suggestions for reforming the legal regulation of the relevant area in Ukraine. Research methods of the study comprises general scientific, comparative, philosophical, and ideological, methods of analysis and special methods. Results: ensuring effective protection of intellectual property rights in cyberspace is a complex task and it must be developed and implemented taking into account the best practices of global leaders in the IT industry. The author made a comprehensive analysis of effective practices for the protection of intellectual property rights in China, the USA, Great Britain, Vietnam, India, Japan and EU countries, providing recommendations for the further implementation of the researched practices in the development of policies, strategies and legal instruments in the field of ensuring the effective protection of intellectual property rights in the digital environment. Discussion: trans-border nature, unlimited by geographical boundaries, negatively affects the protection of easily replicated content. It has also become easier for violators to commit illegal acts due to distinctions in the regulation of relevant issues in different countries. Governors and legislators need to develop and implement effective strategies and policies to mitigate these problems.